Characterisation and utilisation of steel slag for the construction of roads and highways. (8th December 2014) - Aziz, M. M. A.; Hainin, M. R.; Yaacob, H.; Ali, Z.; Chang, F.-L.; Adnan, A. M.
<x content-type="archive" xml:space="preserve">Abstract</x> Steel slags are by-products from steel industries which can be used for the construction of roads and highways. Most of the physical and mechanical properties of steel slags are similar or better compared to conventional crushed stone aggregates. Most of the developed countries have successfully incorporating steel slags as an aggregate in hot mix asphalt, road base, sub-base and soil stabilisation in road works. This paper is a review of the physical, mechanical and chemical characteristics of steel slags and its utilisation in road pavement works. This paper highlights the flaws that need to be addressed, and further studies are required to develop an understanding of the potential of steel slag as a construction material. Hydrophobic property of steel slag provides a good adhesion with bitumen binder and helps to resist against the stripping and other defects of roads. Thus, it enhances a sustainable cost-effective green pavement in highway industry.